2017
DOI: 10.1017/wsc.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage on Control of Wild Oat (Avena fatua) by the Soil-applied Herbicide Pyroxasulfone

Abstract: Wild oat control options are limited in western Canada due to resistance to most common herbicides. Control of wild oat with pyroxasulfone, a soil-applied, very-long-chain fatty-acid inhibitor, was investigated. A series of greenhouse and field experiments were conducted to isolate the effects of vertical seed position, site of herbicide interception, and tillage on wild oat control with pyroxasulfone in comparison with triallate. In greenhouse experiments, wild oat shoot length (soil surface to leaf tip) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The level of resistance to prosulfocarb observed in this field-selected population was similar to a recurrently selected L. rigidum population of Busi and Powles (2013). The RIs for triallate and thiobencarb were slightly higher than for prosulfocarb and EPTC, which could be related to the differences in water solubility and binding capacity among the thiocarbamate herbicides tested (Mangin et al 2017; Westra et al 2014). The EP162 population displayed a level of trifluralin resistance similar to a recent report of 17-fold resistance conferred through a target-site point mutation in an L. rigidum population SLR74 (Fleet et al 2017) and consistent with reported resistance in field-collected populations from across South Australia (Boutsalis et al 2012).…”
Section: Resultsmentioning
confidence: 95%
“…The level of resistance to prosulfocarb observed in this field-selected population was similar to a recurrently selected L. rigidum population of Busi and Powles (2013). The RIs for triallate and thiobencarb were slightly higher than for prosulfocarb and EPTC, which could be related to the differences in water solubility and binding capacity among the thiocarbamate herbicides tested (Mangin et al 2017; Westra et al 2014). The EP162 population displayed a level of trifluralin resistance similar to a recent report of 17-fold resistance conferred through a target-site point mutation in an L. rigidum population SLR74 (Fleet et al 2017) and consistent with reported resistance in field-collected populations from across South Australia (Boutsalis et al 2012).…”
Section: Resultsmentioning
confidence: 95%
“…Other studies have found that tillage can have both a negative and positive effect on weed seed banks: tillage may temporarily incorporate some weed seeds into deeper layers while bringing others to the soil surface where they are exposed to the conditions necessary for germination (Carter and Ivany 2006;Santín-Montanyá et al 2016). A study on wild oat (Avena fatua L.) in Alberta, Canada determined that tillage practices resulted in higher weed pressure for two reasons: first, tillage buried wild oat seeds deeper within the soil profile, thereby limiting their exposure to herbicides (Mangin et al 2016). Secondly, the relatively large seed size of wild oat allows it to germinate from greater depths within the soil, thus negating the benefits of burying the seeds through tillage (Ibid.).…”
Section: Overview Of Weed Management Under Conservation Agriculturementioning
confidence: 99%
“…Reduced rainfall following herbicide application would therefore most likely be the cause of pyroxasulfone failure. Although thiocarbamate herbicides still have a rainfall requirement following application, they require less rainfall following application than pyroxasulfone (Mangin et al 2017). The uptake of thiocarbamate herbicides is also through both the shoots and roots (Fuerst 1987).…”
Section: Effect Of Herbicides On Rigid Ryegrass Density and Seed Prodmentioning
confidence: 99%